2022
DOI: 10.3390/coatings12020119
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Deposition of Amorphous Al2O3-GAP Ceramic Coating with Excellent Microstructure Stability and Uniformity via Atmospheric Plasma Spraying

Abstract: A novel Al2O3-GdAlO3 (GAP) amorphous ceramic coating was in situ prepared via atmospheric plasma spraying (APS). The Al2O3/Gd2O3 sprayable powders possessed excellent sphericity and fluidity after heat treatment at 1173 K without solid-phase reaction, which indicated that the Al2O3-GAP coating deposition process was significantly simplified. The Al2O3-GAP amorphous coating showed high glass transition temperature (1155.1 K), initial crystallization temperature (1179.2 K), local activation energy (847.6 kJ/mol)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Above 30% grain boundary cracking occurred due to the brittleness of the Al2O3 [47]. An amorphous ceramic coating comprising Al2O3-GdAlO3 (GAP) was prepared by APS from sprayable powder precursors [28]. This coating, as described by Qiang Anti-reflective coatings were formed by alternating layers of TiO2/SiO2, as reported by Zambrano et al, as shown in Figure 4 [58].…”
Section: Methods Key Features Referencesmentioning
confidence: 91%
See 1 more Smart Citation
“…Above 30% grain boundary cracking occurred due to the brittleness of the Al2O3 [47]. An amorphous ceramic coating comprising Al2O3-GdAlO3 (GAP) was prepared by APS from sprayable powder precursors [28]. This coating, as described by Qiang Anti-reflective coatings were formed by alternating layers of TiO2/SiO2, as reported by Zambrano et al, as shown in Figure 4 [58].…”
Section: Methods Key Features Referencesmentioning
confidence: 91%
“…Above 30% grain boundary cracking occurred due to the brittleness of the Al 2 O 3 [47]. An amorphous ceramic coating comprising Al 2 O 3 -GdAlO 3 (GAP) was prepared by APS from sprayable powder precursors [28]. This coating, as described by Qiang et al, had an excellent microstructure uniformity and mechanical performance, as shown in Figure 3 temperature-stable coatings which required a transparent scratchproof coating or depositing at room temperature, where scratch resistance was not required.…”
Section: Methods Key Features Referencesmentioning
confidence: 99%
“…Meanwhile, the left boundary of the model was set as a symmetric boundary, and the vertical displacement of the bottom boundary was set to zero. The material properties used in this FEM analysis were obtained from the literature [35][36][37][38].…”
Section: Finite Element Analysismentioning
confidence: 99%
“…Recent studies [21,22] also indicate that it is possible to obtain coatings with the main α-Al 2 O 3 phase by plasma spraying using γ-Al 2 O 3 as a starting powder. These studies show that the variation of process parameters, such as firing frequency and barrel fill volume, affects the ratio of α-Al 2 O 3 and γ-Al 2 O 3 phases in the resulting coatings.…”
Section: Introductionmentioning
confidence: 99%